Female‐dependent transmission of paternal mtDNA is a shared feature of bivalve species with doubly uniparental inheritance (DUI) of mitochondrial DNA. (3rd March 2015) - Machordom, Annie; Araujo, Rafael; Toledo, Carlos; Zouros, Eleftherios; Ladoukakis, Emmanuel D.
Abstract Several species from a number of bivalve molluscan families are known to have a paternally transmitted mitochondrial genome, along with the standard maternally transmitted one. The main characteristic of the phenomenon, known as doubly uniparental inheritance (DUI), is the coupling of sex and mtDNA inheritance: males receive both genomes but transmit only the paternal to their progeny; females either do not have the paternal genome or, if they do, they do not transmit it to their progeny. In the families Mytilidae and Veneridae, both of which have DUI, a female individual is either female‐biased (it produces only, or nearly so, female progeny), male‐biased (it produces mainly male progeny) or non‐biased (it produces both genders in intermediate frequencies). Here we present evidence for a same pattern in the freshwater mussel, Unio delphinus (Unionidae). These results suggest that the maternal control of whether a fertilized egg will develop into a male or a female individual (and the associated feature of whether it will inherited or not inherit the paternal mtDNA) is a general characteristic of species with DUI.